ANALISIS PROPENSITY SCORE MATCHING DAMPAK EKONOMI SERTIFIKASI C.A.F.E. PRACTICES PADA USAHATANI KOPI LINTONG SUMATERA UTARA - Sinaga, Sonitia Verawati; Harianto, Harianto; Suharno, Suharno (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2019)
The C.A.F.E. Practices aims to ensure that coffee is produced from sustainable farming and process by evaluating economic, social, and environmental aspects in the production process. Incentive for farmers following the certification will get better price than those not following certification. This research aims to analyze factors influencing farmer to participate in C.A.F.E. certification. After then, the economic effect of the certification will be analyzed using Propensity Score Matching (PSM) based on significant factors that influence farmers to participate in the certification. To reach that aims, a survey is conducted to 162 Lintong coffee farmers, consisting of 81 people who participate in certification and 81 people who do not participate in the certification. PSM in this research is conducted through psmatch 2 and the nearest neighbor method. Based on the logit analysis, some factors like famers’ age, area, the number of family member, and income outside coffee farming significantly influence farmers’ participation in the certification. The analysis on the effect of certification based on psmatch 2 and the nearest neighbor method after balancing test shows that the variable costs is increase significantly, while the increase in productivity and coffee farming income was not significant.